PENGATURAN HAK NORMATIF BAGI PEKERJA/BURUH MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Joko Nur Sariono; Suhandi Suhandi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
National development is carrying out with final goal to achieve fair and prosperous. We for all Indonesian people. Worker; no exceptions, has an important role in national development. Therefore, the manpower development would also be an crucial thing to do, in order to get higher quality of skilled and trained worker; and to assure their normative rights, such as: the rights to get proper wages and leave, and also health and safety rights. These points has been regulated in UU No. 13 Th. 2003, Lembaran Negara Republik Indonesia Th. 2003 No. 39.